2020
DOI: 10.1111/tri.13793
|View full text |Cite
|
Sign up to set email alerts
|

Influence of donor‐transmitted coronary artery disease on long‐term outcomes after heart transplantation ‐ a retrospective study

Abstract: Background Cardiac allograft vasculopathy (CAV) is an important cause of late mortality after heart transplantation, which may be influenced by preexisting coronary disease (CAD) in the donor heart. Methods The aim of this study was to verify whether CAD in the donor heart had any influence on survival, cardiac‐related adverse events (CRAEs), and coronary disease progression after transplantation. Donor coronary angiography performed in 289 hearts showed absence of CAD in 232 (no‐CAD group) and moderate (≤50%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…being treated for hypertension in the absence of LVH do not appear to impact post-transplant outcomes. Level of Evidence: C. Recommendations regarding donors with coronary artery disease (CAD): 55,[118][119][120][121][122][123][124] (Table 3 Recommendations regarding donors with diabetes: 54,55,58,59,68,69,81,116,117,[128][129][130][131] Class IIa:…”
Section: Chronic Hypertension (Defined By Contemporary Guidelines) Or...mentioning
confidence: 99%
“…being treated for hypertension in the absence of LVH do not appear to impact post-transplant outcomes. Level of Evidence: C. Recommendations regarding donors with coronary artery disease (CAD): 55,[118][119][120][121][122][123][124] (Table 3 Recommendations regarding donors with diabetes: 54,55,58,59,68,69,81,116,117,[128][129][130][131] Class IIa:…”
Section: Chronic Hypertension (Defined By Contemporary Guidelines) Or...mentioning
confidence: 99%
“…8,30,31 In Europe where the donor shortage is more acute, the use of donors with nonobstructive coronary disease has been reported and outcomes seem to be similar long term. 32…”
Section: Discussionmentioning
confidence: 99%
“…8,30,31 In Europe where the donor shortage is more acute, the use of donors with nonobstructive coronary disease has been reported and outcomes seem to be similar long term. 32 In October 2018, UNOS implemented a new prioritization system that emphasizes patients who qualify for temporary mechanical circulatory support over patients with stable durable left ventricular assist devices or inotrope dependence. As well, the artificial use of donor service areas and local organ allocation was dissolved in preference for distance-based concentric circles around the donor hospital to eliminate disparities based on organ procurement organization efficiency or geographic constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Factors not associated with increased CAV include donor history of cocaine use, donor ischemic time, and post-HTx AMR ≥pathologic grade 1 during first year or PGD, irrespective of severity [3,43,86,123,124]. Donorderived CAD does not seem to accelerate progression of CAV [50]. Although CAV is associated with sudden cardiac death and with lower survival rates at 3 and 10 years post-HTx, especially if developed within the first year, CAV rates and survival have generally improved [3,118,123].…”
Section: Cardiac Allograft Vasculopathymentioning
confidence: 93%
“…Diabetic status of donors does not affect recipient survival post-HTx, regardless of insulin dependence [49]. Singlecenter studies found that carefully-selected recipients of allografts from donors with moderate coronary artery disease (CAD) or coronary artery calcification may have similar short-and long-term survival and freedom from cardiac adverse events compared to their counterparts [50,51]. Longer donor ischemic time, especially ≥4-5 hours, is associated with higher short-and long-term mortality rates after HTx [11,16,18,[25][26][27][28][29]36,44,52].…”
Section: Donor Risk Factorsmentioning
confidence: 99%